Integrating ChatGPT into the English Essay Writing Class: Perceptions of EFL Preservice Teachers - Nunung Nurhayati; Iyan Hayani (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The incorporation of ChatGPT as a supplementary tool for teaching writing has gained considerable attention. This study aims at exploring perceptions of EFL preservice teachers regarding the use of ChatGPT in the English essay writing class. Adopting a qualitative approach, the research involved seven EFL preservice teachers who participated on a voluntary basis. Data were collected through semi-structured interviews. The participants were third-semester students enrolled in the English Essay Writing course within an English education program. The findings revealed a variety of experiences and difficulties, including the tool effectiveness in enhancing essay organization and clarity, concerns pertaining to its ethical issue and differing levels of reliance. In addition, some participants valued ChatGPT for its effectiveness and feedback, but others drew attention to its shortcomings in terms of encouraging creative thinking. Moreover, the results highlight the significance of striking a balance between AI support and human direction. Limitations of the study are acknowledged, and recommendations for future research are provided.